Regional Economic Outlook, October 2020, Asia and Pacific : Navigating the Pandemic: A Multispeed Recovery in Asia. (International Monetary Fund, 2020)
The coronavirus disease (COVID-19) pandemic is still unfolding around the globe. In Asia, as elsewhere, the virus has ebbed in some countries but surged in others. The global economy is beginning to recover after a sharp contraction in the second quarter of 2020, as nationwide lockdowns are lifted and replaced with more targeted containment measures.